Implementasi Strategi Email Blast dalam Promosi Produk Sertifikasi HRD Online di CV. ABC - Mochammad Rakha Abimanyu; Istian Kriya Almanfaluti (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study addresses the challenge of email deliverability in the implementation of email blast as a digital marketing strategy for promoting online HRD certification products at CV. ABC. Despite its operational efficiency, email blast campaigns often fail to reach recipients’ primary inboxes, reducing promotional effectiveness. This research aims to describe the preparation process, implementation, and effectiveness of email blast strategies applied by CV. ABC during an internship period. A descriptive qualitative approach was employed, with data collected through direct observation and documentation of email marketing activities, including database management, platform usage, content delivery, and inbox placement outcomes. The findings indicate that email blast campaigns conducted using automated platforms such as kirim.email and Jagoan Hosting were not fully effective, as a significant portion of promotional emails were classified into spam or promotional folders. The results suggest that overly promotional content characteristics and the use of mass-sending platforms influenced email filtering systems. As an alternative, manual email delivery with limited recipients demonstrated a higher likelihood of reaching the main inbox. The study concludes that while email blast enhances efficiency in promotional activities, its effectiveness depends on appropriate content design and delivery methods, requiring strategic adjustments to improve email inbox deliverability.